PERAN RETRIBUSI PARKIR DALAM PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) KOTA SOLOK: ANALISIS PERTUMBUHAN DAN EFEKTIVITAS - Sefli Diana Roza; Esi Sriyanti; Syalshabilla Syalshabilla (STKIP Persada Khatulistiwa Sintang, 2026)
This study aims to analyze the growth and effectiveness of parking retribution revenue toward Local Own Source Revenue of Solok City. The research was conducted at the Transportation Agency of Solok City, with the population consisting of financial reports on parking retribution revenue. The research sample includes data on targeted and realized parking retribution revenue as well as the realized Local Own Source Revenue of Solok City. Data were collected through interviews and documentation, using both primary and secondary data. The data analysis techniques employed include growth analysis, effectiveness analysis, and contribution analysis. The results show that the growth of parking retribution revenue in Solok City during the period 2021–2024 was unstable, with the highest growth of 157% occurring in the third semester of 2022. In terms of effectiveness, parking retribution revenue has not yet achieved an optimal level, with average effectiveness rates of 33% in 2021, 85% in 2022, 44% in 2023, and 47% in 2024. Indicating that parking retribution revenue still plays a relatively minor role in supporting the Local Own Source Revenue of Solok City. This study focuses on one type of Local Retributions, namely roadside parking fees, with an observation period of 2021–2024. Furthermore, the analysis is limited to measuring the growth and effectiveness of parking retribution revenue, and therefore does not comprehensively cover other factors that could potentially influence Local retribution revenue.